Prevalencia de Parasitosis Intestinal en Gestantes atendidas en los Centros Asistenciales del Distrito de Tarapoto, periodo Marzo Agosto 1993 - Águila Bartra, Diomar Del (1994)
Intestinal parasitosis occupies a leading role in the third world countries, constituting one of the major problems in public health So much so that some infectious diseases have disappeared, as have declined otr and many can be controlled successfully, this has occurred diseases caused by viruses and bacteria, but not with disease caused by parasites that are causes of debilitating, acute, chronic, often Mortals (4) intestinal parasites like worms have special importance. to have detrimental effects on the health of the mother and fetus, causing frequent anemia predispose to other diseases and contribute to the diminished mental capacity of the individual physical, compromising their productivity (2). They are therefore important not only from a medical standpoint but also social and economic, to be a major factor in underdevelopment. In life. human influence many ecological, social and economic phenomena, which is accentuated ron rapid population growth experienced by cities through migration, rural dweller moved to the city in search of a better material welfare that have few resources are grouped into neighborhoods, human sentamientos, characterized. by extreme poverty deficient in basic living, economic, health and medical infrastructure, such defecation to occur. outfield polluted soil, favoring the life cycle of parasites whole .. This problem is present throughout our territory, but its prevalence depends on the geographical region, environmental sanitation quality housing, cultural socioeconomic levels, hygiene Personal and collective quality of life, overcrowding and promiscuity own environment aspects: physical and chemical characteristics of the soil, temperature, humidity, rainfall, vegetation, among others (12). Prevalence rates of intestinal parasitic current exhibit similarity to those found 50 years ago in poor communities in tropical countries (4). A study in Guatemala was observed that (a helminth infection in pregnant women is associated with intrauterine growth retardation, in this study it was concluded that up to 10% of intrauterine growth can be attributed to infection by parasites mothers malnourished (10). the present work is performed for the first time in our country allow to present the profile of the disease and its prevalence.